Meningoensefalitis TB Pada Laki-Laki Usia 20 Tahun dengan Human Immunodeficiency Virus : Sebuah Laporan Kasus - Fitriyani, Fitriyani; Saragih, Andriani Dearta (CV. Jasa Sukses Abadi, 2024)
Meningoencephalitis is a neurological condition that contains both symptoms of meningitis and encephalitis – inflammation of the meninges (lining of the CNS) and inflammation of the brain tissue itself. Fever, headache, meningismus, changes in mental status, neurological deficits and/or seizures are symptoms of meningoencephalitis. Mycobacterium tuberculosis infection in the central nervous system can cause several diseases, one of which is meningitis. Meningitis is an inflammatory condition of the meninges caused by an infective agent. If this meningeal infection process affects the brain parenchyma, it is called meningoencephalitis. Meningoencephalitis patients who present with decreased consciousness should be considered whether they have tuberculous meningitis (TB), especially if there is a history of pulmonary tuberculosis, alcohol use, Human Immunodeficiency Virus (HIV) infection or other conditions associated with impaired immune response. The diagnosis of TB meningoencephalitis is often delayed due to late presentation of the clinical picture, resulting in high morbidity and mortality rates. TB meningoencephalitis is also associated with a high incidence of sequelae that persist for a long time and tends to have a poor prognosis, so immediate treatment or management is needed for patients. We report the clinical presentation and management of a case of a man with meningoencephalitis and a history of HIV disease. A 20 year old man with the main complaint of loss of consciousness and pain throughout the body. Additional complaints include fever, dizziness, trembling in both hands accompanied by nausea and vomiting since 8 days of SMRS. The patient was then taken to the emergency room at Abdul Moeloek Regional Hospital with complaints of loss of consciousness, body shaking and pain throughout the body. Cough (-), runny nose (-), vomiting (-), diarrhea (-), head trauma (-), coma consciousness. Previously the patient had been diagnosed with HIV. Physical examination showed meningeal stimulation (+), Management of meningoencephalitis using antibiotic therapy. Several neurological disorders can occur in Meningoencephalitis patients.